2011
DOI: 10.1021/cm201197j
|View full text |Cite
|
Sign up to set email alerts
|

Multiconstituent Synthesis of LiFePO4/C Composites with Hierarchical Porosity as Cathode Materials for Lithium Ion Batteries

Abstract: Monolithic, three-dimensionally ordered macroporous and meso-/microporous (3DOM/m) LiFePO 4 /C composite cathodes for lithium ion batteries were synthesized by a multiconstituent, dual templating method. Precursors containing sources for lithium, iron, and phosphate, as well as a phenol-formaldehyde sol and a nonionic surfactant were infiltrated into a colloidal crystal template. Millimeter-sized monolithic composite pieces were obtained, in which LiFePO 4 was dispersed in a carbon phase around an interconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 57 publications
0
64
0
Order By: Relevance
“…40,41,42 As little as 3 % carbon has been reported, 43 but similarly composites with 50-50 metal oxide-carbon have exhibited good performance as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 electrodes. 44,45 One challenge associated with design of electrode materials is that the performance is driven by a plethora of both physical and chemical variables.…”
Section: Resultsmentioning
confidence: 99%
“…40,41,42 As little as 3 % carbon has been reported, 43 but similarly composites with 50-50 metal oxide-carbon have exhibited good performance as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 electrodes. 44,45 One challenge associated with design of electrode materials is that the performance is driven by a plethora of both physical and chemical variables.…”
Section: Resultsmentioning
confidence: 99%
“…[ 182 ] Even though a phenolic resin is generally considered a hard carbon precursor, the graphitic domains in the composite were quite large ( ∼ 5 nm), and the sample was able to support current densities as high as 2720 mA g − 1 . The large graphitic domains were attributed to the presence of Fe 2 + in the precursor mixture, which can act as a catalyst for the formation of graphitic carbon.…”
Section: A Secondary Conductive Phase Improves Conductivity and High mentioning
confidence: 99%
“…They have found that the discharge capacity is strongly affected by the amount of carbon residue and sintering temperature. After optimization, LiFePO 4 /C composites with 1.87 wt % of carbon exhibited a best electrochemical performance with capacities of 140 mAh/g at C/10 and 84 mAh/g at 5 C. Vu et al (2011) synthesized monolithic, three-dimensionally ordered macroporous and meso-/microporous (3DOM/m) LiFePO 4 /C composite cathodes by a multiconstituent, dual templating method. In this composite, LiFePO 4 is dispersed in a carbon phase around an interconnected network of ordered macropores.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%